Business Strategy of Layer Chicken Business in the New Normal Era in The Bali Province - Nyoman Suparta; I Gusti Agus Maha Putra Sanjaya; Dewa Putu Semara Yana (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2022)
This study aims to provide a business strategy for laying hens in the New Normal era in the Province of Bali. This research is expected to produce recommendations for the right strategy to be applied to laying hens in the Province of Bali to help farmers face the New Normal era and able to increase breeders' income. This research was conducted in 3 central districts of laying hens in Bali Province using a survey method. The research location was determined by purposive sampling technique. The results of the IFAS-EFAS analysis showed an internal factor value of 3.65 and an external factor value of 3.31 indicating the position of the laying hen business in Bali Province is in quadrant I, namely growth and build strategy. Alternative strategies that need to be increased more intensively are: 1) Expansion of market share outside Bali (West Region to Jakarta and Eastern Region to East Nusa Tenggara), 2) Expansion of business scale by increasing capital, 3) Selecting less productive laying hens.